Increased neutrophil/lymphocyte ratio in testicular cancer - Aytaç Şahin; Tuncay Toprak; Musab Ali Kutluhan; Yasin Vural; Ahmet Ürkmez; Ayhan Verit (Archivio Italiano di Urologia e Andrologia, 2019)
Objective: Testicular cancers, which are less common than other cancers, are important in terms of being seen in young people. Physical examination, imaging, laboratory and tumor markers are used for diagnosis. There are some studies of some blood parameters that can be involved in inflammation and tumorogenesis. We retrospectively compared hematological values measured in our patients who were diagnosed with testicular tumor in comparison with patients with similar age group who underwent varicocelectomy repair. Materials and methods: This cross-sectional retrospective study included 120 patients who underwent radical inguinal orchiectomy for testicular tumor between January 2010 and December 2018, and 171 patients who underwent varicocelectomy as a control group. Patients with an active infection and hematological disorders were excluded from the study. We evaulated hematological parameters including neutrophil (NEU), lymphocyte (LYM), platelet (PLT) count, and mean platelet volume. The study was conducted on 291 patients. divided in two groups: tumor (n = 120) and varicocele (n = 171). Results: There was no statistically significant difference between the groups in terms of PLT / lymphocyte ratio and mean platelet volume (MPV) levels (p > 0.05). The neutrophil /lymphocyte ratio (NLR) of the tumor group was significantly higher than the varicocele group (p = 0.001; p < 0.05). There was a statistically significant difference between the tumor stages in terms of PLT / Lymphocyte ratios (p = 0.006; p < 0.05). Conclusions: There was only a statistically significant increase in NLR values in the testicular tumor group compared to the varicocele group. Larger, randomized controlled studies are needed at this field.